Integrasi Maqasid Al-Shariah Dalam Manajemen Strategik Pendidikan: Sebuah Krangka Konseptual - Rohman, Muhammad Kholilur; saputra, Yusril Ihza; Kamil, Moh.; Abrar, Muhammad Thoiful; Holidi, Moh.; Muhlas, Moh.; Mudarris, Badrul (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyze how Maqasid Al-Shariah is integrated into the strategic management of education at Madrasah Aliyah Negeri 1 Probolinggo, and how its values ​​influence the institution's governance, organizational culture, and evaluation system. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation analysis. Data were then analyzed through data condensation, data presentation, and verification using content and interpretive analysis. The results show that the values ​​of Maqasid Al-Shariah such as hifz al-din, hifz al-nafs, hifz al-‘aql, hifz al-nasl, and hifz al-mal have been consistently implemented in the formulation of the vision, institutional governance, and performance evaluation of the madrasah. The application of these values ​​not only strengthens the moral and spiritual integrity of the madrasah community but also increases managerial effectiveness through a transparent, participatory, and equitable work system. The implications of this research confirm that the integration of Maqasid Al-Shariah can serve as a new conceptual framework for developing strategic management of Islamic education, oriented not only toward academic achievement but also toward the welfare, character, and sustainability of spiritual values ​​within educational institutions.